Impact of COVID-19 Pandemic to Finance Shared Services Employees’ Performance of a Government Contracting Company in Dubai, United Arab Emirates - Silva, Mark Anthony H; Briones, Jesus P (International Journal of Economics, Business and Management Studies, 2022)
This study assessed the implications of the COVID-19 pandemic to the work lifestyle (work prioritization, work satisfaction, and work performance), and psychological and physical health of the finance shared services department workforce of a government contracting company in Dubai, United Arab Emirates. The data were collected through a survey questionnaire sent via Google form to 20 finance shared services employees. The findings of the study revealed that majority of the respondents are female, with ages from 41-50 years old, single, working on either accounts payables or accounts receivables, regular employees, and have been staying with the company for 6 years and above. As for the work lifestyle, the employees generally disagreed on the indicators for work prioritization, work satisfaction, and work performance. Further, as for the psychological impact, employees indicated that they worry that they might get sick or their loved ones due to the virus. Similarly, they showed constant worry regarding their physical health. The study also found out that there is no significant correlation between work performance and work satisfaction to the respondents’ demographic profile as well as having no correlation of employees’ psychological and physical health to respondents’ demographic profile. On the other hand, there is a significant correlation between the work performance and work satisfaction to employees’ psychological and physical health.